Common Risk Factors Responsible for Acute Kidney Injury among Children: Experience at Medical University in Bangladesh - Luna, Sharmin Akter; Sultana, Jakia; Mamun, Abdullah Al; Begum, Afroza; Rahman, Md Habibur; Roy, Ranjit Ranjan (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Acute kidney injury can occur among the younger children due to different reasons. Objective: The purpose of the present study was to find out the risk factors and primary disease responsible for acute kidney injury among younger children. Methodology: This cross-sectional study was conducted in the Department of Paediatric Nephrology with the collaboration of Paediatric Gastroenterology, Paediatric Neurology, Paediatric Neonatology and Microbiology and Immunology at Bangabandhu Sheikh Mujib University, Dhaka, Bangladesh from May 2018 to July 2019 for a period of one year. Patients with the age group of 1 month to 17 years who were at risk of AKI, and admitted in the inpatient department of Pediatrics and allied at Bangabandhu Sheikh Mujib University, Dhaka, Bangladesh in both sexes were selected as study population. To detect AKI, serum creatinine was measured at 0 h (baseline), 48 h and 5th day respectively. Result: A total number of 42 patients, who fulfilled the inclusion criteria were enrolled in this study. The risk factors of AKI was mainly pre renal in 60% (n=9) cases, mostly due to nephrotoxic drugs followed by hypovolemia. Renal causes were in 40% (n=6) cases. Among these 50% cases due to amikacin and 50% cases due to use of radiocontrast agent. Most patients were with renal disease which was 30(58%) cases. Among them 28(93.0%) cases were nephrotic syndrome and 2(7.0%) cases were hydronephrosis. However, 7(13%) cases were cardiac disease presented with congenital heart disease who used radiocontrast agent. Conclusion: In conclusion most common risk factors of acute kidney injury among younger children is pre-renal causes which are due to nephrotoxic drugs. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 42-46